2003
DOI: 10.1063/1.1540612
|View full text |Cite
|
Sign up to set email alerts
|

Selective and reversible entrapment of He and Ne in NaA zeolite at atmospheric pressure

Abstract: The He͑Ne͒/NaA-zeolite system was studied using temperature programmed desorption mass spectrometry ͑TPD-MS͒ with a supersonic molecular-beam inlet. Controllable, stable, and reversible entrapment of He and Ne by the ␤ cages of NaA zeolite was experimentally achieved at ambient pressure and around 200°C. Decapsulation of either He or Ne from NaA is shown to be of a doublet character, indicating on the occurrence of effectively two classes of ␤ cavities: completely blocked cages, never previously observed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…By observing a series of N 2 isotherms at different temperatures, we can assign T C at around 266 K. It is noteworthy that even below T C the N 2 loading on KCHA1 is nonzero although it is relatively low (e.g., 0.02 mmol/g at 195 K), which is believed to represent adsorption on the external surface sites of chabazite or a small minority of unblocked cavities resulting from lattice defects. Previous encapsulation work shows that there are two classes of sites in type A zeolite, that is, α-cage and β-cage, which can be accessible to gas molecules at different temperatures. ,,, In the case of the potassium chabazite/N 2 system, although the kinetic diameter of N 2 molecule and the effective aperture diameter of D6R unit are comparable (0.364 nm versus 0.26 nm), the limited void volume of D6R unit probably prevents N 2 diffusion . Therefore, we believe that the effective sites of KCHA1 for N 2 are on the external surface and in the supercavities with the former accessible in the entire temperature range, while the latter is only accessible above a certain temperature ( T C ).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…By observing a series of N 2 isotherms at different temperatures, we can assign T C at around 266 K. It is noteworthy that even below T C the N 2 loading on KCHA1 is nonzero although it is relatively low (e.g., 0.02 mmol/g at 195 K), which is believed to represent adsorption on the external surface sites of chabazite or a small minority of unblocked cavities resulting from lattice defects. Previous encapsulation work shows that there are two classes of sites in type A zeolite, that is, α-cage and β-cage, which can be accessible to gas molecules at different temperatures. ,,, In the case of the potassium chabazite/N 2 system, although the kinetic diameter of N 2 molecule and the effective aperture diameter of D6R unit are comparable (0.364 nm versus 0.26 nm), the limited void volume of D6R unit probably prevents N 2 diffusion . Therefore, we believe that the effective sites of KCHA1 for N 2 are on the external surface and in the supercavities with the former accessible in the entire temperature range, while the latter is only accessible above a certain temperature ( T C ).…”
Section: Resultsmentioning
confidence: 87%
“…Breck 26 observed that a variation in vibration amplitude of 0.01-0.02 nm in the temperature range of 80-300 K is reasonable in the case of zeolite A structure, and an expansion or dilation of 0.03 nm in the aperture diameter could result from thermal vibration effect alone. Saig et al 27 later tried to verify the structural dilation of zeolite A using molecular dynamics and demonstrated that lattice vibration can yield large fluctuation of zeolite apertures, thus enhancing permeability and observed deviations as high as 7% in the case of sodalite at 503 K. Therefore, we believe that higher temperature facilitates the diffusion of N 2 molecules through the pore window due to elevated cation mobility and structure dilation.…”
Section: Effect Of Cation Typementioning
confidence: 86%
See 1 more Smart Citation
“…In general, depending on zeolite grade, the TPD c profiles are seen to consist of up to two principal decapsulation peaks. The low- T peaks, centered around −170 °C in the cases of dehydrated 4A and 5A, were previously attributed to α and β encapsulations, respectively. , These low-T peaks however, depict poor encapsulations in the sense that the closure of the O 6 windows of the β cage, and certainly of the wider O 8 windows of the α cages, in 5A and 4A, respectively, is ineffective for an efficient quantitative entrapment of Ne and moreover for He, even at temperature as low as LN 2 . Upon evacuation of dried 4A and 5A samples at LN 2 , most of the pre-admitted gas slowly discharges, strongly indicating the imperfect enclosure of the relevant apertures in these grades …”
Section: Resultsmentioning
confidence: 81%
“…The experimental details of the temperature-programmed decapsulation (TPD c ) measurements were previously discussed and described. , In the present study, the effect of dehydration on He and Ne encapsulation was studied for the three family members of type-A zeolites. Samples of as purchased hydrated grades, each weighing ca.…”
Section: Methodsmentioning
confidence: 99%